Content analysis of DBA and PhD dissertations in business. Issue 4 (19th May 2018) - MacLennan, Helen; Piña, Anthony; Gibbons, Sean
ABSTRACT: The doctor of business administration (DBA) degree is widely considered as a professional doctorate or professional doctoral degree that is designed to prepare business practitioners. The doctor of philosophy (PhD) in business, by contrast, is thought to prepare research scholars and higher education faculty members. Prior research conducted by the authors comparing the curriculum of DBA and PhD programs, analyzing accreditation and regulation of the degree programs and examining the terminal degrees of business faculty, did not support the theoretical difference between the two degrees. This study consisted of an analysis of 147 DBA versus 151 PhD dissertations. The analysis indicated a significant group mean difference in the number of PhD versus DBA dissertations in institutions with an R1 classification by the Carnegie Commission on Higher Education. However, no significant correlations nor group mean differences were found in methodology choice, sample size, or research type (applied vs. basic), based on the degree type (DBA vs. PhD).